Modern Orthodox Judaism : a documentary history - Eleff, Zev (JPS anthologies of Jewish thought., 2016)
Modern Orthodox Judaism offers an extensive selection of primary texts documenting the Orthodox encounter with American Judaism that led to the emergence of the Modern Orthodox movement. Many texts in this volume are drawn from episodes of conflict that helped form Modern Orthodox Judaism. These include the traditionalists' response to the early expressions of Reform Judaism, as well as incidents that helped define the widening differences between Orthodox and Conservative Judaism in the early twentieth century. Other texts explore the internal struggles to maintain order and balance once Orthodox Judaism had separated itself from other religious movements. Zev Eleff combines published documents with seldom-seen archival sources in tracing Modern Orthodoxy as it developed into a structured movement, established its own institutions, and encountered critical events and issues--some that helped shape the movement and others that caused tension within it. A general introduction explains the rise of the movement and puts the texts in historical context. Brief introductions to each section guide readers through the documents of this new, dynamic Jewish expression.